Moving beyond self‐report data collection in the natural environment: A review of the past and future directions for ambulatory assessment in eating disorders. Issue 10 (16th July 2019) - Smith, Kathryn E.; Mason, Tyler B.; Juarascio, Adrienne; Schaefer, Lauren M.; Crosby, Ross D.; Engel, Scott G.; Wonderlich, Stephen A.
Abstract: Objective: In recent years, ecological momentary assessment (EMA) has been used to repeatedly assess eating disorder (ED) symptoms in naturalistic settings, which has allowed for increased understanding of temporal processes that potentiate ED behaviors. However, there remain notable limitations of self‐report EMA, and with the rapid proliferation of technology there are ever‐increasing possibilities to improve ambulatory assessment methods to further the understanding and treatment of EDs. Therefore, the purpose of this review was to (a) systematically review the studies in EDs that have utilized ambulatory assessment methods other than self‐report, and (b) provide directions for future research and clinical applications. Method: A systematic literature search of electronic databases was conducted, and data regarding study characteristics and methodological quality were extracted. Results: The search identified 17 studies that used ambulatory assessment methods to gather objective data, and focused primarily on autonomic functioning, physical activity, and cognitive processes in ED and control groups. Discussion: Together the literature demonstrates the promise of using a range of ecologically valid ambulatory assessment approaches in EDs, though there remains limited research that has utilized methods other than self‐report (e.g., wearable sensors), particularly in recent years. Going forward, there are several technology‐enhanced momentary assessment methods that have potential to improve the understanding and treatment of EDs. Resumen: En años recientes, la evaluación momentánea ecológica (en inglés, ecological momentary assessment (EMA)) ha sido utilizada repetidamente para evaluar los síntomas de trastorno de la conducta alimentaria (TCA) en ambientes naturalistas, lo que ha permitido un incremento en el entendimiento de los procesos temporales que potencían las conductas de trastornos alimentarios. Sin embargo, todavía hay notables limitaciones del autoreporte EMA y con la rápida proliferación de la tecnología hay todavía mayores posibilidades de mejorar los métodos de evaluación ambulatoria para avanzar el entendimiento y el tratamiento de los TCAs. Objetivo: Por lo tanto, el propósito de esta revisión fue 1) revisar sistemáticamente los estudios en TCAs que han utilizado métodos de evaluación ambulatoria además del auto‐reporte, y 2) proveer las pautas para futuras investigaciones y aplicaciones clínicas. Método: Se realizó una búsqueda sistemática de la literatura en las bases de datos electrónicas, y los datos con las características del estudio y calidad metodológica fueron extraídos. Resultados: La búsqueda identificó 17 estudios que utilizaron métodos de evaluación ambulatoria para recopilar datos objetivos y se centraron principalmente en el funcionamiento autónomo, la actividad física y los procesos cognitivos en los grupos de control y de TCA. Discusión: En conjunto, la literatura demuestra la promesa de utilizar una variedad de abordajes de evaluación ambulatoria ecológicamente válidos en los TCA, aunque sigue habiendo investigaciones limitadas que han utilizado métodos distintos al autoinforme (por ejemplo, sensores portátiles), particularmente en los últimos años. En el futuro, hay varios métodos de evaluación momentánea mejorados con tecnología que tienen potencial para mejorar la comprensión y el tratamiento de los TCA.